Beginnen met Rodin. (Antwerpen : Openluchtmuseum voor beeldhouwkunst Middelheim, 1989)
Bourdelle, E.A. ; Despiau, Charles ; Maillol, Aristide ; Meunier, Constantin ; Minne, Georges ; Renoir, Auguste ; Rodin, Auguste ; Rosse, Medardo ; Wijnants, Ernest ; Wouters, Rik
boek